STUDI EKSPERIMENTAL PENGARUH JUMLAH SUDU DAN PENGGUNAAN END PLATE TERHADAP CUT IN SPEED TURBIN ANGIN SAVONIUS HELIKS - Hermawan Yudha Prasetya; Danar Susilo Wijayanto; Taufik Wisnu Saputra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
This study aims to analyze the effect of variations in the number of blades and the use of end plates on the cut in speed of Helical Savonius wind turbine. The method used in this research is the experimental method. The variables used in this study are variations in wind speed from 1 to 5 m/s with intervals of 0.5 m/s. Variations in the number of blades are 2,3, and 4 blades. Variations in the use of end plates and without end plates. The results of this study was found that variations in the number of blades and the use of end plates affect the cut in speed of helical Savonius wind turbine. The fewer the number of turbine blades, the better the turbine's cut in speed will be. 2 blade’s Helical Savonius wind turbine with end plate is turbine variation that is able to produce best cut in speed of 1.97 m/s, compared to other variations.